Biofortification of wheat, rice and common bean by applying foliar zinc fertilizer along with pesticides in seven countries - Ram H. (2017)
© 2016, Springer International Publishing Switzerland. Aims: Rice (Oryza sativa L.), wheat (Triticum aestivum L.) and common bean (Phaseolus vulgaris L.) are major staple food crops consumed worldwide. Zinc (Zn) deficiency represents a common micronutrient deficiency in human populations, especially in regions of the world where staple food crops are the main source of daily calorie intake. Foliar application of Zn fertilizer has been shown to be effective for enriching food crop grains with Zn to desirable amounts for human nutrition. For promoting adoption of this practice by growers, it is important to know whether foliar Zn fertilizers can be applied along with pesticides to wheat, rice and also common bean grown across different soil and environmental conditions. Methods: The feasibility of foliar application of zinc sulphate (ZnSO 4 .7H 2 O) to wheat, rice and common bean in combination with commonly used five fungicides and nine insecticides was investigated under field conditions at the 31 sites-years of seven countries, i.e., China, India, Pakistan, Thailand, Turkey, Brazil and Zambia. Results: Significant increases in grain yields were observed with foliar Zn/foliar Zn + pesticide (5.2–7.7 % of wheat and 1.6–4.2 % of rice) over yields with no Zn treatment. In wheat, as average of all experiments, higher grain Zn concentrations were recorded with foliar Zn alone (41.2 mg kg −1 ) and foliar Zn + pesticide (38.4 mg kg −1 ) as compared to no Zn treatment (28.0 mg kg −1 ). Though the magnitude of grain Zn enrichment was lesser in rice than wheat, grain Zn concentrations in brown rice were significantly higher with foliar Zn (24.1 mg kg −1 ) and foliar Zn + pesticide (23.6 mg kg −1 ) than with no Zn (19.1 mg kg −1 ). In case of common bean, grain Zn concentration increased from 68 to 78 mg kg −1 with foliar Zn alone and to 77 mg kg −1 with foliar Zn applied in combination with pesticides. Thus, grain Zn enrichment with foliar Zn, without or with pesticides, was almost similar in all the tested crops. Conclusions: The results obtained at the 31 experimental site-years of seven countries revealed that foliar Zn fertilization can be realized in combination with commonly-applied pesticides to contribute Zn biofortification of grains in wheat, rice and common bean. This agronomic approach represents a useful practice for the farmers to alleviate Zn deficiency problem in human populations.